Knowledge, Attitudes and Practices towards Medical Waste Management among Health Workers at Mityana District Hospital, Mityana District. A Cross-sectional Descriptive Survey - Immaculate Namutebi; Zaitune Nanyunja (Student's Journal of Health Research, 2022)
Introduction:  The Ministry of Health (MoH) of Uganda with support from the Government of Uganda highly advocates for proper Hospital waste management, this is because poor medical waste disposal and management pose serious health consequences and significant impact on the health workers, patients, and waste handlers and the environment. However, there is a general paucity of information on the level of knowledge, attitude, and practices of health workers towards medical waste management in Mityana district hospital and Uganda at large.  Objective:  The purpose of the study, therefore, was to ascertain the knowledge, attitude, and practices of health workers towards hospital waste management in Mityana district hospital. Methods:  A cross-sectional descriptive survey was carried out among 116 health workers at Mityana District hospital. Data were collected using a self-administered questionnaire and were analyzed using SPSS version 21. Statistical significance of association between variables was assessed using the Chi-square test at p<0.05. Ethical clearance was obtained from the Research Ethics Committee of Makerere University. Results:  All 116 respondents returned the completed questionnaires. sixty-three (54.3%) males and fifty-three (45.7%) females. The mean age of respondents was 36.3 years. 81 (69.8%) had heard of hospital waste management while, 35(30.2%) had never had about it. Out of the total respondents, 83 (71.6%) were aware that medical wastes are classified and segregated into their bags according to colors, although the majority of 74(63.8%) reported storage containers are not cleaned every day. In general, the respondents had average knowledge of medical waste management although 40.5 % lacked some knowledge at all. The majority of 101 (87.1%) use latex gloves when handling waste. Conclusion:  Most of the respondents knew what healthcare waste management means, but very few practiced appropriate healthcare waste management. Recommendation: Health education and training are recommended for the health care workers periodically and regularly.